Kampung Naga Tasikmalaya Menjaga Alam Dengan Keyakinan Pada Norma dan Tradisi - Eulis Entin; Denny Adrian Nurhuda; Nunuy Nurjanah; Retty Isnendes (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Kampung Naga is an indigenous village in West Java that still upholds the values of ancestral heritage. This research discusses how the description of the Kampung Naga community settlement and the value system and norms carried out by the Kampung Naga community and the correlation between the value system and community behavior reflected in the settlement towards natural preservation. With an ethnographic approach, this research describes and interprets cultural phenomena that reflect the view of life of the Kampung Naga community. Data were collected through literature study, field observations, and interviews. The literature study involved archives, articles, and books, while field data was obtained through involved observation and in-depth interviews, which recorded the mythology and spatial layout of Kampung Naga. The data were then identified and processed inductively, based on existing concepts, values and beliefs. The results showed that the people of Kampung Naga still strongly uphold ancestral customs, which help maintain the balance of nature and prevent environmental damage. They value customs as norms in action and behavior, utilize local produce, and inherit Sundanese manners well, as well as showing typical Sundanese hospitality or commonly called soméah hadé ka sémah, which reflects hospitality and respect for guests.